Pendampingan Daur Ulang Limbah Kemasan Minyak Goreng Sebagai Media Tanam Toga - Hermanto, Hermanto; Elvina, Elvina; Utama, Annisa Dwi; Pratama, Ihsan Putra; Andriyani, Rizki (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
This community service activity aims to raise awareness about the importance of recycling and waste management, while teaching valuable skills in recycling plastic packaging into environmentally friendly polybags. This activity was carried out on July 2 - August 2, 2024 in Bawang Village, Punduh Pidada District, Pesawaran Regency. This community service activity was carried out through socialization, counseling and recycling processing of cooking oil packaging waste as a planting medium for herbal medicine. The results of community service activities have shown success in increasing community participation, promoting sustainable resource utilization, and reducing the amount of plastic waste in the environment